2003
DOI: 10.1016/s0092-8674(03)00645-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E Ablation in the Mouse

Abstract: E type cyclins (E1 and E2) are believed to drive cell entry into the S phase. It is widely assumed that the two E type cyclins are critically required for proliferation of all cell types. Here, we demonstrate that E type cyclins are largely dispensable for mouse development. However, endoreplication of trophoblast giant cells and megakaryocytes is severely impaired in the absence of cyclin E. Cyclin E-deficient cells proliferate actively under conditions of continuous cell cycling but are unable to reenter the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
625
6
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(674 citation statements)
references
References 50 publications
39
625
6
4
Order By: Relevance
“…Cdk2 is known to be active in complex with cyclin E at the G 1 -S boundary, and in complex with cyclin A during S-phase progression (Shapiro, 2006). Although it has been described that cdk2 is not an essential gene in the mouse, (Berthet et al, 2003;Geng et al, 2003;Ortega et al, 2003;Tetsu and McCormick, 2003) an overexpression of cdk2 with associated cyclins has been shown in several tumors (Al-Aynati et al, 2004;Olofsson et al, 2004). Furthermore, cdk2 has been recently found to be required for centrosome duplication in mammalian cells (Matsumoto et al, 1999;Matsumoto and Maller, 2004) suggesting that inhibition of cdk2 activity would be an effective anticancer approach.…”
Section: Discussionmentioning
confidence: 99%
“…Cdk2 is known to be active in complex with cyclin E at the G 1 -S boundary, and in complex with cyclin A during S-phase progression (Shapiro, 2006). Although it has been described that cdk2 is not an essential gene in the mouse, (Berthet et al, 2003;Geng et al, 2003;Ortega et al, 2003;Tetsu and McCormick, 2003) an overexpression of cdk2 with associated cyclins has been shown in several tumors (Al-Aynati et al, 2004;Olofsson et al, 2004). Furthermore, cdk2 has been recently found to be required for centrosome duplication in mammalian cells (Matsumoto et al, 1999;Matsumoto and Maller, 2004) suggesting that inhibition of cdk2 activity would be an effective anticancer approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated normal fetal development following disruption of the D-and E-type cyclins, Cdk4, Cdk6 and Cdk2, suggesting that the individual functions of these genes were not essential for cell cycle progression [27,28]. One possible explanation is that cyclins that promote entry into the S phase in yeast are deleted This cyclin complementation has been demonstrated in mammalian cells [29].…”
Section: Discusssionmentioning
confidence: 99%
“…44 In the presence of elevated E2F, associated with cancer, inhibition of CDK2 can lead to apoptosis. 45 Given recent findings, 1,[9][10][11][12][13][14][15][16]46 there is no reason to think that CDK2 is universally needed to all normal cells. Likely, certain types of normal cells are CDK2 independent.…”
Section: Cdk2: Clinical Applicationsmentioning
confidence: 99%